Costs of incident non-hip osteoporosis-related fractures in postmenopausal women from a payer perspective - Barcelos, Anabela (2023)
Funding Information: Open access funding provided by FCT|FCCN (b-on). The study was supported by an unrestricted research grant from Amgen. Publisher Copyright: © 2023, The Author(s).